Screened moments and extrinsic in-gap states in samarium hexaboride - W. T. Fuhrman (Nature Portfolio, 2018)
The unconventional behaviour of samarium hexaboride has been difficult to explain in part because of differences between samples. Here the authors use gadolinium to exemplify that hard to avoid impurities introduce a low energy density of states that may explain earlier observations.